NOVEL INSIGHTS INTO THE MECHANISM OF ACTION OF EXCLUSIVE ENTERAL NUTRITION IN CROHN'S DISEASE: PRE-CLINICAL STUDY IN A RODENT MODEL OF CROHN'S-LIKE COLITIS. (22nd January 2022) - Geesala, Ramasatyaveni; Lin, You-Min; Zhang, Ke; M'Koma, Amosy; Cohn, Steven; Shi, Xuan-Zheng
Abstract: BACKGROUND AND AIMS: Exclusive enteral nutrition (EEN) is the only established dietary therapy for Crohn's disease (CD). However, mechanisms of action of EEN in CD are not clear. CD is characterized by recurrent transmural inflammation in the gut. Mechanical stress, associated with inflammatory cell infiltration, edema, fibrosis, and obstruction, is inevitably present in CD tissue. We hypothesized that transmural inflammation causes mechanical stress, which induces expression of mechanosensitive genes such as IL-6 and COX-2 in the gut, and that EEN treatment attenuates inflammation by alleviating the effect of mechanical stress-induced expression of proinflammatory genes in CD. METHODS: CD-like colitis was induced by intracolonic instillation of TNBS (65 mg/kg in 250 μL of 40% ethanol) into the distal colon of 8∼10 weeks old SD rats. Control rats were treated with intracolonic saline instillation. We fed the control and colitis rats with either normal pellet food or EEN with Ensure liquid diet ad lib. Rats were euthanized 7 days after treatments. RESULTS: (1) TNBS colitis rats presented decreased body weight, increased disease activity and inflammation index of the colon in pellet food treated rats, which were dramatically improved by EEN treatment. (2) EEN did not significantly affect body weight in control rats, though it dramatically reduced fecal weight by 84.5(±4.3)%, and increased fecal water content by 29.8(±1.3)%. (3) In the solid food fed rats, TNBS treatment induced a localized transmural inflammation with narrowed lumen in the site of instillation (site I) (Figure 1). This led to a distended colon segment (site P) prior to site I, and a non-distended segment (site D) distal to site I. Expression of IL-6 and COX-2 mRNAs was increased significantly (p<0.01) by 111(±44) and 13.1(±2.5)-fold in site I of CD rats, compared to controls. Importantly, the IL-6 and COX-2 mRNA expression was also significantly increased in the distended site P [228(±72) and 16.6(±4.3)-fold], but not in site D (Figure 2). The increased expression of IL-6 and COX-2 occurred mainly in the colonic smooth muscle cells (SMC). (4) However, EEN treatment with Ensure Regular prevented lumen distention in colitis rats. The increase of IL-6 and COX-2 expression in colitis was attenuated drastically in sites I and P (Figure 2). Treatment with other types of liquid diet (Ensure Clear or rodent liquid diet) had similar effects. (5) Expression of IL-6 and COX-2 was highly inducible by mechanical stretch in cultured colonic SMC in vitro and by lumen distention in colon obstruction. CONCLUSIONS: Mechanical stress plays a critical role in gut inflammation by inducing expression of mechanosensitive proinflammatory mediators in CD-like colitis. EEN treatment reduces inflammation in CD by alleviating the effects of mechanical stress on expression of genes such as IL-6 and COX-2.